Temperature dependence of electronic parameters of organic Schottky diode based on fluorescein sodium salt - Yahia, I. S.; Farag, A. A. M.; Yakuphanoğlu, Fahrettin; Farooq, W. A. (Elsevier Science Sa, 2011)
The electrical properties of an organic Schottky diode based on fluorescein sodium salt were investigated by current density-voltage and capacitance-voltage measurements. The crystal structure of fluorescein sodium salt, FSS in powder form was analyzed by X-ray diffraction method. X-ray diffraction results showed that the fluorescein sodium salt has a polycrystalline structure with a monoclinic system. The current density-voltage and capacitance-voltage characteristics of Al/FSS Schottky diode were investigated in the temperature range of 300-400 K. The diode exhibits a rectifying behavior, indicating the formation of the Schottky type junction at the interface of Al/FSS. The predominant charge transport mechanism of the Al/FSS Schottky diode was discussed and the proposed current injection processes was presented. The temperature dependence of the calculated acceptor concentration, the built-in potential and the width of the depletion region of Al/FSS Schottky barrier was also determined. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Organic semiconductor; Al/FSS Schottky diode; Rectification; Current-voltage; Capacitance-voltage